State Estimation for Standard Neural Network Models with Time-Varying Delays - Jin Zhu; Tai-Fang Li; Huanqing Wang (Complexity)
The paper deals with the issue of state estimation for standard neural network models with time-varying delays. A new augmented vector with the derivative of the state is introduced in the Lyapunov–Krasovskii functional. The state estimation criteria are obtained by constructing the suitable Lyapunov–Krasovskii functional; meanwhile, the observer gain and the controller gain are derived in terms of linear matrix inequality. The free matrix-based integral inequality is utilized to handle the integral terms, and the zero equation is added to the derivative of the Lyapunov–Krasovskii functional, which decreases the conservatism. The effectiveness and feasibility of the proposed methods are demonstrated by two numerical examples.